Revolutionizing the Governance of Village-Owned Enterprises (BUMDES): SIABDes Taxion Software to Increase Transparency - Adji Koerniawan, Koenta; Tresna Murti, Galuh; Urip Wardoyo, Dwi (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: This community service initiative inspires a brighter future by enhancing governance and financial transparency of Village-Owned Enterprises (BUMDES) in Indonesia, specifically BUMDES Patandang Cangkuang Kulon. By fostering innovation and strengthening governance, it empowers rural communities to thrive through improved management practices and technology. Contribution: The project provides a replicable model for enhancing BUMDES governance through participatory training and digital financial tools. Method: A participatory approach was used, involving needs assessment, focus group discussions, training sessions, and implementation of the SIABDes Taxion software for accounting and PPh21 tax reporting. Results: The program involved 27 participants from four BUMDES. Post-training evaluation showed an average post-test score of 82.05% and a participant satisfaction rate of 100%, indicating increased capacity in financial governance and system adoption. Conclusion: The program addressed key challenges in BUMDES financial governance. Sustained mentoring and adequate resource support remain essential for long-term success.